Spectral observation of agarwood by infrared spectroscopy: The differences of infected and normal Aquilaria microcarpa - Danang Sudarwoko Adi; SUNG-WOOK HWANG; DWI AJIAS PRAMASARI; YUSUP AMIN; BERNADETA AYU WIDYANINGRUM; TEGUH DARMAWAN; ERIS SEPTIANA; WAHYU DWIANTO; JUNJI SUGIYAMA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Adi DS, Hwang SW, Pramasari DA, Amin Y, Widyaningrum BA, Darmawan T, Septiana E, Dwianto W, Sugiyama J. 2020. Spectral observation of agarwood by infrared spectroscopy: The differences of infected and normal Aquilaria microcarpa. Biodiversitas 21: 2893-2899. This study was conducted to evaluate and to determine the potential spectral band assignments that influenced the differentiation of normal and infected agarwood of Aquilaria microcarpa using Fourier Transform Infrared Spectroscopy (FTIR) and Fourier Transform Near-Infrared Spectroscopy (FTNIR). The results showed that the differences in band intensity on FTIR were identified as C=O stretching (lignin), COO-stretching (hemicellulose), aromatic skeletal vibration (lignin), and C-H bending vibration. The increasing absorbances of infected agarwood were supposed as the change on the wood tissues due to the releasing resinous compound. The C-O bond (aromatic alkane) and stretching (ether), C-C stretching (aromatic alkane), and C-H bond (aromatic ring) which related to the scented fragrance of agarwood have appeared on the FTIR spectra. Multivariate analysis with principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA) of the second derivative NIR spectra at the wavenumber 8,000-4,000 cm-1 showed that normal and infected agarwood was successful to be separated. Discriminant model one-on-one classification exhibited good performances as the R2 performance (R2P) values was 0.99. There were eight major wood components which contributed to the separation based on NIR spectra, where lignin, hemicellulose, and xylans were the most valuable chemical compound.